Republic of Serbia : Request for Stand-By Arrangement; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Serbia. (IMF Staff Country Reports; Country Report ;, 2009)
With global financial turmoil increasingly spilling over into Serbia, the authorities have requested a 15-month Stand-By Arrangement (SBA), which they intend to treat as precautionary. The authorities' program aims at safeguarding macroeconomic and financial stability, in view of the global financial turmoil. The authorities' SBA-supported program responds to the abrupt deterioration in global financial sentiments. Safeguarding macroeconomic and financial stability are the primary objectives of the program, and the authorities recognize that policies will need to be strengthened across the board.